Does advance care planning in addition to usual care reduce hospitalisation for patients with advanced heart failure: A systematic review and narrative synthesis. (December 2018) - Kernick, Lucy A; Hogg, Karen J; Millerick, Yvonne; Murtagh, Fliss E M; Djahit, Ayse; Johnson, Miriam
Background: People with advanced heart failure have repeated hospital admissions. Advance care planning can support patient preferences, but studies in people with heart failure have not been assessed. Aim: To evaluate the literature regarding advance care planning in heart failure. Design: Systematic review and narrative analysis (PROSPERO CRD42017059190). Data sources: Electronic databases were searched (1990 to 23 March 2017): MEDLINE(R), Cochrane Library, CINAHL and Scopus. Four journals were hand searched. Two independent researchers screened against eligibility criteria. One reviewer extracted all data and a sample by a second. Quality was assessed by Cochrane Risk of Bias or the Critical Appraisal Skills Programme Tool for Cohort Studies. Results: Out of the 1713 articles, 8 were included representing 14, 357 participants from in/outpatient settings from five countries. Two randomised controlled trials and one observational study assessed planning as part of a specialist palliative care intervention; one randomised controlled trial assessed planning in addition to usual cardiology care; one randomised controlled trial and one observational study assessed planning in an integrated cardiology–palliative care model; one observational study assessed evidence of planning (advance directive) as part of usual care and one observational study was a secondary analysis of trial participants coded Do Not Attempt Cardiopulmonary Resuscitation. Advance care planning: (1) reduced hospitalisation (5/7 studies); (2) increased referral/use of palliative services (4/4 studies); and (3) supported deaths in the patient-preferred place (2/2 studies). Conclusion: Advance care planning as part of specialist palliative care reduces hospitalisation. Preliminary studies of planning integrated into generic care, accessing specialist palliative care support if needed, are promising.